Pemanfaatan Canva sebagai Media Desain Visual untuk Mengembangkan Kemampuan Komunikasi Visual Siswa di SMK Ma'arif NU 1 Purwokerto - Aditya Pratama; Muhammad Akhsan Daffala; Hilmi Aditya Aflah; Ghois Abdullah Akmal; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The use of visual design media in schools, particularly vocational high schools, remains suboptimal. This community service activity aimed to improve students' ability to use Canva as a visual design tool to support information delivery at SMK Ma'arif NU 1 Purwokerto. The activity employed a descriptive approach combining socialization and hands-on practice. Participants consisted of 20 students who attended the session on April 30, 2026. Data were collected through observation and documentation of students' design outputs, assessed based on three indicators: color selection, typography use, and layout arrangement. The results showed that 80% of students (16 out of 20) demonstrated measurable improvement across all three aspects after the training, with color selection at 80%, typography at 75%, and layout at 85%. Students were able to produce more structured and communicative visual media compared to their initial work. These findings suggest that Canva can serve as a practical tool to support visual communication skills in a school setting.